A PROBE INTO COMPREHENSION AND USE OF ASSESSMENT BY SECONDARY EFL TEACHERS IN CHINA - Huang Jian (English Review: Journal of English Education, 2014)
Abstract: The purpose of this study is to explore Chinese secondary EFL teachers’ comprehension and use of assessment, including formative assessment (FA) and summative assessment (SA). Assessment has a great impact on students’ learning. The role of FA for improving learning has been well documented (Black Wiliam, 1998, Hattie Timperley, 2007, Shute, 2008; Wiliam et al., 2004) and teachers’ summative assessment practices also have the potential to positively influence students and teachers (Biggs, 1998; McMillan, 2003). Thanks to its value for learning and teaching, assessment has been emphasized in many national educational documents in China such as National English Curriculum Standards (MoE, 2001 2011). Yet little researches have been done so far to investigate how secondary EFL teachers in China understand and implement FA and SA. This study, via a qualitative and quantitative analysis of questionnaire questions, reveals some specific patterns in teachers’ understanding and application of assessment: their consistency and inconsistency with the discourse of mainstream assessment literature. The findings are expected to provide implication for development of professional teacher preparation program and teachers’ self-reflection.Keywords: formative assessment, summative assessment, secondary EFL teachers